2019
DOI: 10.35940/ijrte.d5186.118419
|View full text |Cite
|
Sign up to set email alerts
|

Single Edge Notch Bend (SENB) of Kenaf/Fibreglass Hybrid Composites

S. Yunus,
Z. Salleh*,
Y. M. Taib
et al.

Abstract: Kenaf is known for many years as a typical crop that can be used in various applications such as in automotive, and building structure. Along with the depletion and environmental issues raised nowadays by excessively used of man-made synthetic fibres make the natural fibre to become popular and favourable to be implemented. This paper discusses on the development of long kenaf fibre reinforced polyester matrix composite. Total weight of about 40% fibre fraction was selected. In this study, the addition of abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was observed that although there were improvements in the mechanical and physical properties, the significance of chemical changes (such as an increase in the crystalline index, influence on the crystalline size) to the structure of the natural fibre was also significant). Also, Yunus et al (2019) studied the fracture toughness of Kenaf and Fibre glass hybrid composites at up to 40% fibre loading and results of the study showed the significant effect of fiber glass (which had better surface properties than the Kenaf) on the fracture toughness of the material, reinforcing the need for a more efficient and non-corrosive means of natural fiber surface treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that although there were improvements in the mechanical and physical properties, the significance of chemical changes (such as an increase in the crystalline index, influence on the crystalline size) to the structure of the natural fibre was also significant). Also, Yunus et al (2019) studied the fracture toughness of Kenaf and Fibre glass hybrid composites at up to 40% fibre loading and results of the study showed the significant effect of fiber glass (which had better surface properties than the Kenaf) on the fracture toughness of the material, reinforcing the need for a more efficient and non-corrosive means of natural fiber surface treatment.…”
Section: Introductionmentioning
confidence: 99%